2012
DOI: 10.3989/tp.2012.12086
|View full text |Cite
|
Sign up to set email alerts
|

Approach to disability in a population from the Argar Culture

Abstract: A new research field is being developed on disability in Archaeology and Physical Anthropology, which is investigated in this article in the context of the Argaric Culture. More than 200 skeletons, coming from sites in Granada province (Castellón Alto, Fuente Amarga, Cuesta del Negro, Terrera del Reloj and Cerro de la Encina), were studied, finding four with signs of physical impairment: one male and one female who must both have used a walking aid, and two males with shoulder dislocations. All four individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similar considerations have been postulated in studies concerning individuals from the Iberian Peninsula during the Bronze Age, who showed clear signs of disability, having required care to survive. They were buried following the usual funeral rites; then it is assumed that they were not rejected but considered community members at the time of their death (Roca et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar considerations have been postulated in studies concerning individuals from the Iberian Peninsula during the Bronze Age, who showed clear signs of disability, having required care to survive. They were buried following the usual funeral rites; then it is assumed that they were not rejected but considered community members at the time of their death (Roca et al, 2012).…”
Section: Discussionmentioning
confidence: 99%